Simple, cost-effective technique for portable digital eletrocorticography - PAULO R. M. DE BITTENCOURT; MARCOS C. SANDMANN; MARLUS S. MORO; JOÃO C. DE ARAÚJO (Arquivos de Neuro-Psiquiatria)
We revised 16 patients submitted to epilepsy surgery using a new method of digital, real-time, portable electrocorticography. Patients were operated upon over a period of 28 months. There were no complications. The exam was useful in 13 cases. The low installation and operational costs, the reliability and simplicity of the method, indicate it may be useful for defining the epileptogenic regions in a variety of circumnstances, including surgery for tumors, vascular malformations, and other cortical lesions associated with seizure disorders.